Curriculum construction and teaching practice: an approach (Praxis Educativa, 2012)
This text presents the first steps of a research process carried out at ìEscuela Superior de Comercio Manuel Belgranoî, UNC, which is based on a study on curriculum design done over the years 1995 and 1999 and its further implementation. The process of construction of the new curriculum is set in the political context provided by the educational transformation legislated by Federal Act 24195. A review of the institutional conditions at the time of its implementation, limits and internal conflicts that emerged from the reorganization of the curricular spaces and the incorporation of new ones, is also provided. This process opened up new questions that disclosed the complexity and lack of linearity of the curriculum as social construct and led to a first approach to teaching practices through the voice of teachers and students. The challenge lies in the construction of a methodological approach to study the articulation of what is prescribed by law and the actual practice in context.
Keywords: high school; research; prescribed curriculum; teaching practices; construction